ANALISIS PENGARUH PENDEKATAN SAINTIFIK DAN PEMBERIAN REWARD TERHADAP PERKEMBANGAN ANAK USIA DINI - Amelia Vinayastri; Khusniyati Masykuroh; Eka Fitriani; Rizka Anugerahwaty (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2019)
The scientific approach is done through observing, asking, trying, analyzing and communicating to students. The role of the teacher in the scientific approach as a facilitator to achieve the learning objectives, in addition the teacher can also provide motivation through the provision of rewards in the form of appreciation that is beneficial for early childhood development, for example gifts, various stickers, or a compliment. Besides that activities that use a scientific approach and the provision of rewards, students can think scientifically, and can develop the character of students according to the stage of development. The study was conducted at TK Aisyiyah Bustanul Atfhak, East Jakarta Municipality with a sample of 71 people using the survey method by distributing instruments. The results of the study of multiple linear regression equations obtained positive coefficient values which means the giving of rewards and scientific approaches have a positive influence on early childhood development. Giving rewards contributed 19.2% to early childhood development and the scientific approach contributed 64.9% to child development. Thus the conclusion of this study is the provision of reward and scientific approach has a proportion of influence on early childhood development by 59.6%.